GORDON MOORE AND ARTHUR ROCK'S LAWS IN THE DIGITAL ECONOMY, AN ANALYSIS OF HOW LAWS ARE MADE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article covers the history of microcircuits in every device used today and the importance of Gordon Moore's and Arthur Rock's laws in the history of microcircuits. We will consider the content of the laws and the history of their formation. We will find out the answer to this question whether these laws are still in force today.